THE EFFECT OF USING INFOGRAPHICS AND STUDENTS’ READING INTEREST ON THEIR READING COMPREHENSION AT SMAN 16 PEKANBARU - Dian Eka Hertavira (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This research was done by applying experimental research and the design used was factorial design 2x2. The aims of this research were (1) to find out whether there is any different effect of students’ reading comprehension between an experimental and control class. (2) To find out the different on students’ reading comprehension between students who have high reading interest in an experimental class and a control class. (3) To find out the different on students’ reading comprehension between students who have low reading interest in an experimental class and a control class. (4) To find out whether there is any interaction between teaching strategies and reading interest on students’ reading comprehension. The samples were two classes of eleventh grade students of Social 1 and Social 2 of SMAN 16 Pekanbaru. The writer took the sample as cluster random sampling technique. The total sample was 60 students. The forms of the test were reading comprehension test and questionnaire. Finally, the results of the research show that: first, there was the significant score (sig.) 0.02 < 0.05 in students’ reading comprehension. It means that there is significant difference on students’ reading comprehension between an experimental class and control class. Second, there was no significant difference on students’ reading comprehension between students who have high reading interest in an experimental and control class. The sig value was 0.841 > 0.05. Third, there was significant difference on students’ reading comprehension between students who have low reading interest in an experimental and control class. The sig value was 0.03 > 0.05. Last, the sig value was 0.045 < 0.05. It means that there was an interaction between teaching strategy and reading interest on students’ reading comprehension at SMAN 16 Pekanbaru.Key words: Infographics, Reading Interest, Reading Comprehension